(untitled) (Itinera, 2024)
The essay discusses the workings of disgust in Michael Haneke’s cinema. Beginning with major philosophical and psychoanalytic reflections and through innovative contemporary consideration, the categories of disgust in the director’s films are examined, taking as examples the most exemplary films in this regard and especially those that propose an idea of disgust as a mechanism for distancing the viewer and reflecting on contemporary nihilism.